PEMETAAN DAERAH RAWAN BENCANA KECAMATAN BELAWAN DENGAN APLIKASI SISTEM INFORMASI GEOGRAFIS - Kartika Indah Sari; Darlina Tanjung (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2022)
District Medan Belawan often subjected to tidal flooding. This is due to because the region is located on the coast of the beach and the surface of the ground is lower than the surface of the ocean. Some of the factors that cause the occurrence of tidal flooding are global warming, high rainfall, deforestation of mangroves, the utilization of ground water for excessive, and green open space in Medan city is only available to 10% of the total area. One disaster mitigation efforts required Mapping of disaster risk as a benchmark in preparing the program and activity. Furthermore, mapping the risk of flood disaster can provide input to the government of the municipality of the field in an effort to cope with the flood disaster that occurred in district Medan Belawan. Mapping disaster-prone areas district belawan with the application of information systems geographical conducted to classify the flood zone is located in district of Medan Belawan base the physical conditions that affect the risk of flood disaster. In addition, for identifying the number of roads, the population and buildings affected by the floods done by using the results of the mapping flood prone areas based on spatial, so we knew which roads affected by flooding as much as 160 roads with a length of road 38.595 meters and the building affected by the flood reached 10.939 units spread over six districts.